1999
DOI: 10.1097/00006123-199904000-00046
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spondylotic Myelopathy: Functional and Radiographic Long-term Outcome after Laminectomy and Posterior Fusion

Abstract: Cervical laminectomy with posterior fusion/fixation proved useful in the treatment of patients with CSM with straight or lordotic spines and multilevel compression. This therapy addresses the dynamic and compressive forces that are important in the pathogenesis of CSM, resulting in minimal complications and possible improvement in long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(69 citation statements)
references
References 35 publications
0
68
0
1
Order By: Relevance
“…8) In fact, postoperative MR imaging of this technique demonstrated kyphotic change. Therefore, simple laminectomy and posterior fusion is not indicated in cases like ours.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…8) In fact, postoperative MR imaging of this technique demonstrated kyphotic change. Therefore, simple laminectomy and posterior fusion is not indicated in cases like ours.…”
Section: Discussionmentioning
confidence: 90%
“…Since the laminoplasty method is popular in Japan, 7,9,10,12,14) we think that there is no reason not to combine plate fixation and laminoplasty with multilevel iliac bone graft rather than laminectomy and plate fixation. 1,8) This combined technique may save an additional anterior approach operation for stabilization or correction of the kyphosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decompression via laminectomy is a commonly employed surgical intervention, although many clinicians have reported that the longitudinal results can be less than ideal. Deleterious outcomes associated with laminectomy include development of progressive cervical kyphosis, instability, perineural adhesions and late neurologic deterioration [1,15,16,19,20,24,30,33,34,40]. Laminoplasty eliminates many of these complications and achieves decompression of the spinal cord by allowing the cord to migrate posteriorly away from the compressive lesion, while preserving the posterior bone stock and architecture [22,23].…”
mentioning
confidence: 99%